Pengaruh Promosi Jabatan Terhadap Kinerja Karyawan (Penelitian Lapangan di Lembaga Amil Zakat Infaq dan Sedekah PUI) - Yasir Muharram Fauzi (Jurnal Maps (Manajemen Perbankan Syariah), 2022)
This research is motivated by problems that occur in the field where organizational dynamics according to the initial hypothesis have problems regarding polarization and optimization of the ability to empower Human Resources, especially in terms of promotions that must be able to build and improve employee performance. In this case the author examines the effect of promotion on employee performance at Lazis PUI. The purpose of this research is to find out how big the influence of job promotion on employee performance at Lazis PUI. The research method used in this study is to use quantitative associative methods. The data of this study were obtained from primary data by distributing questionnaires and then processed using the SPSS application. The results showed that the variable of job promotion showed an influence on employee performance at Lazis PUI, it can be concluded that the effect of job promotion on employee performance at Lazis PUI was 0.059 or 5.90% and the t value = 1.627 < t table value = 2.021 with the significance of 0.111 > 0.05 does not significantly affect employee performance. The predictive ability of these variables on the level of employee performance in this study was 0.202 or 20.2% and t count = 3.258 > t table = 2.021 with a significance of 0.002 < 0.05. While the rest is influenced by other factors that are not included in the study.